PENGARUH PERBANDINGAN DAUN KELOR DENGAN BUNGA ROSALLA DAN SUHU PENYEDUHAN TERHADAP MUTU MINUMAN HERBAL KELOR ROSELLA (The Effect of Ratio of Moringa Leaves with Rosella Flowers and Brewing Temperature on the Quality of Moringa-Rosella Herbal Drink) - Egidya Friskila; Hotnida Sinaga; Ismed Suhaidi (Universitas Sumatera Utara, 2018)
ABSTRACT The purpose of this research was to determine the effect of the ratio of moringa leaves with rosella flowers and the best percentage of brewing temperature in making moringa-rosella drink on the quality of the herbal drink. This research used compeletely randomized factorial design of two factors, namely : the ratio of moringa leaves to rosella flowers (K) : (100%:0% ; 75%:25% ; 50%:50% ; 25%:75% ; 0%:100%) and brewing temperature (P) : (60oC, 70oc, 80oC). Parameters analyzed were moisture content, colour index, vitamin C levels ,antioxidant activity, hedonic colour values, flavour, taste, and consumer acceptance.The results showed that the ratio of moringa leaves with rosella flowers has very significant effect on moisture content, colour index ,antioxidant activity, hedonic colour values, flavour, taste, and consumer acceptance. The effect of brewing temperature has very significant effect on vitamin C levels and antioxidant activity. Based on hedonic colour values, flavor, taste and consumer acceptance, the ratio of moringa leaves with rosella flowers (25%:75%) with 80oC brewing temperature produces the best quality of the herbal drink. Keywords : brewing temperature,drink herbal, moringa leaves, rosella flowers. ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh perbandingan daun kelor dengan bunga rosella dan suhu penyeduhan terhadap mutu minuman herbal kelor-rosella yang tepat dalam pembuatan minuman herbal. Penelitian ini menggunakan rancangan acak lengkap faktorial 2 faktor yaitu perbandingan daun kelor dengan bunga rosella (K): (100%:0% ;75%:25% ; 50%:50% ; 25%:75% ; 0%:100%) dan suhu penyeduhan (P) : (60oC ; 70oC ; 80oC). Parameter yang dianalisa adalah kadar air, indeks warna, kadar vitamin C, aktivitas antioksidan, nilai hedonik warna, aroma, rasa, dan penerimaan konsumen.Hasil penelitian menunjukkan bahwa perbandingan daun kelor dengan bunga rosella memberikan pengaruh berbeda sangat nyata terhadap kadar air, indeks warna, aktivitas antioksidan, nilai hedonik warna, aroma, rasa, dan penerimaan konsumen. Pengaruh suhu penyeduhan memberikan pengaruh berbeda sangat nyata terhadap kadar vitamin C dan aktivitas antioksidan. Berdasarkan nilai hedonik warna, aroma, rasa, penerimaan konsumen, perbandingan daun kelor dengan bunga rosella (25%:75%) dengan suhu penyeduhan 80oC menghasilkan kualitas minuman herbal yang terbaik. Kata kunci : bunga rosella, daun kelor, minuman herbal, suhu penyeduhan.